Wood addition in the hatchery and river environments affects post‐release performance of overwintering brown trout. (29th October 2018) - Watz, Johan; Calles, Olle; Carlsson, Niclas; Collin, Teemu; Huusko, Ari; Johnsson, Jörgen; Nilsson, Per Anders; Norrgård, Johnny; Nyqvist, Daniel
Abstract: Habitat structural complexity affects the behaviour and physiology of individuals, and responses to the environment can be immediate or influence performance later in life through delayed effects. Here, we investigated how structural enrichment, both pre‐release in the hatchery rearing environment and post‐release in the wild, influenced winter growth and site fidelity of brown trout stocked into side channels of a regulated river. Experiencing structural enrichment in the rearing environment during 3 months in autumn had no pre‐release effect on growth, but a delayed positive effect after release during the subsequent winter. Moreover, trout recaptured in wood‐treated sections of the side channels had grown more than trout recaptured in control sections. Wood enrichment in the side channels also increased overwinter site fidelity. These results show that adding structure during a relatively short period may alter growth trajectories, and adding wood to side channels is a cost‐effective method to enhance winter habitat carrying capacity for juvenile salmonids in regulated rivers.